2022
DOI: 10.1371/journal.pone.0268216
|View full text |Cite
|
Sign up to set email alerts
|

Proportionate clinical burden of respiratory diseases in Indian outdoor services and its relationship with seasonal transitions and risk factors: The results of SWORD survey

Abstract: Background The Global Burden of Disease data suggest that respiratory diseases contribute to high morbidity in India. However, the factors responsible for high morbidity are not quite clear. Therefore, the Seasonal Waves Of Respiratory Disorders (SWORD) study was planned to estimate the point prevalence due to respiratory diseases in Indian OPD services and its association with risk factors and change in seasons. Methods In this point prevalence observational multicenter study conducted during 2017–18, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…10,19,24 Bronchial asthma was more common in females, which is consistent with previous research, indicating a potential role of reproductive hormones in the reversal of male predominance at puberty. 23,[26][27][28] Conversely, TB and COPD were more prevalent in males, consistent with previous reports in Nigeria. 10,18,19 There was a slight male preponderance observed in ILD and lung cancer, whereas Alasia et al found a female preponderance in ILD, which they attributed to the higher incidence of rheumatic disease in females.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…10,19,24 Bronchial asthma was more common in females, which is consistent with previous research, indicating a potential role of reproductive hormones in the reversal of male predominance at puberty. 23,[26][27][28] Conversely, TB and COPD were more prevalent in males, consistent with previous reports in Nigeria. 10,18,19 There was a slight male preponderance observed in ILD and lung cancer, whereas Alasia et al found a female preponderance in ILD, which they attributed to the higher incidence of rheumatic disease in females.…”
Section: Discussionsupporting
confidence: 89%
“…COPD remains the leading cause of respiratory disease-related deaths, and it contributes significantly to frailty and geriatric medicine, as demonstrated by this study. 1,3,23,26 The differences in the age distribution of these respiratory diseases may be attributed to various factors, including environmental exposures, genetic predisposition, and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…11,34,45 Similar to this, the Seasonal Waves of Respiratory Disorders study discovered strong correlations between seasonal variation and a high prevalence of TB, with symptoms worsening slightly in the summer and exacerbating in the autumn as a result of climatic variations in various parts of India. 46 Similarly, research has revealed that atmospheric temperature is an important factor and has a significant association with the progression of TB during the summer and monsoon seasons (Fig. 4).…”
Section: The Burden Of Tuberculosis In Different States Of Indiamentioning
confidence: 89%
“…6), which may be attributed to men's more intense outdoor activities and women's greater likelihood of accessing health services. 1,3,4,20,38,41,46,54,55 In fact, many PTB patients used dangerous sputum disposal techniques, which are dominant in male and illiterate patients from lower socioeconomic groups. 1,22,31,[41][42][43][44]56 Fig.…”
Section: The Burden Of Tuberculosis In Different States Of Indiamentioning
confidence: 99%
“…7 Like regional variation, household-level variation in the prevalence of ARIs among children under-five is also significant in LMICs. 8,9 In particular, household-level factors such as using cooking fuel, having a separate kitchen, ventilation, WASH (water, sanitation, and hand washing) practices, household wealth quintile, and tuberculosis among household members are significant predictors of ARIs. 10,11 Household wealth-based inequality in ARIs among under-five children is also noteworthy in highly focused ARI-prone regions like sub-Saharan African and South Asian countries.…”
Section: Introductionmentioning
confidence: 99%